Disease Detection System from Heart Sounds - Liyanaarachchi, M.R.; Muthalif, F.A.; Perera, K.I.S.; Selvarathnam, M.; Dayananda, N.W.N. (University of Jaffna, 2011)
This paper presents a methodology to diagnose some heart diseases which can be identified using heart sounds. As the first stage, audio files in . wav format are acquired using an electronic stethoscope and entered to a database with patient symptoms. Prominent features and statistical parameters needed for disease detection are extracted from the heart sound samples using some algorithm. Patient's heart sound fde and symptoms are given as inputs to the developed software for analysis to find out the diseases